Digital transformation of vocational schools: problem analysis - Vasyl I. Kovalchuk; Svitlana V. Maslich; Larysa G. Movchan; Valerii V. Soroka; Svitlana H. Lytvynova; Olena H. Kuzminska (Academy of Cognitive and Natural Sciences, 2022)
Modern society is characterized by a significant impact of information technologies on all spheres of human life. In a special way, the processes of digital transformation affect educational institutions, including vocational (vocational and technical) ones. Now vocational (vocational and technical) education occupies an important place in the sector of the country's economy, prioritizing effective training of highly qualified labourers in the state policy of Ukraine. Nowadays, the professional activity of labourers incorporates an intellectual component related to working with electronic devices, artificial intelligence systems, etc. Monitoring of the labor market shows that a skilled worker of the XXI century should be able to think critically, process information analytically, and work with mechatronics systems. The analysis of the European experience in training qualified workers reflects a certain lag of domestic institutions in terms of digital supply. At the same time, the level of teachers' digital competence at vocational (vocational and technical) education institutions needs improving. As a result, the issues of digital transformation for educational institutions are urgent and topical. Provision of modern digital equipment, formation and development of digital competence of all participants in the educational space are becoming the main tasks of teaching stuff in the current conditions. In a special way, the tasks set become relevant during the period of quarantine restrictions, when educational institutions mainly work on distance and mixed forms of teaching.